PAPR Reduction in NC-OFDM Based Cognitive Radio System Using Signal Cancelation and Tone Reservation (International Journal of Engineering and Computer Science, 2017)
High data rate wireless access is demanded by many applications. It requires more bandwidth for higher data rate transmission in any of the system. With promising technology and ever-increasing wireless devices, the spectrum is becoming scarcer day by day. In this case, using noncontiguous orthogonal frequency division multiplexing(NC-OFDM) and cognitive radio(CR) for spectrally efficient transmission are an alternative solution. High peak-to-average power ratio (PAPR) and large spectrum sidelobe power are two main drawbacks of this system. In this paper, we propose a novel signal cancelation (SC) method followed by tone reservation for joint PAPR reduction and sidelobe suppression in NC-OFDM-based CR systems. The key idea of the proposed method is to dynamically extend part of the constellation points on the secondary user (SU) subcarriers and add several SC symbols on the primary user (PU) subcarriers to generate the appropriate cancelation signal for joint PAPR reduction and sidelobe suppression. The joint PAPR reduction and sidelobe suppression can be consider as quadratically constrained quadratic program (QCQP) in SC method to obtain its optimal cancelation signal. The main idea of tone reservation method is to keep a small set of tones for PAPR reduction.